Effect of land use type on metals accumulation and risk assessment in soil in the peri-urban area of Beijing, China. Issue 1 (2nd January 2016) - Xu, Li; Lu, Anxiang; Wang, Jihua; Ma, Zhihong; Pan, Ligang; Feng, Xiaoyuan
ABSTRACT: Heavy metal concentrations of As, Cd, Cu, Hg, Ni, Pb, and Zn were investigated for 107 soil samples collected from crop land, orchard land, greenhouse land, and wood land in the peri-urban area of Beijing, China. The mean concentrations of As, Cd, Cu, Hg, Ni, Pb, and Zn in all soil samples were 8.40, 0.20, 24.7, 0.08, 25.0, 23.0, and 77.1 mg/kg, dw, respectively. Among the four land use types, the Cd concentration in greenhouse land was significantly higher than the other three kinds of land uses ( p < .05), and Cu and Zn concentrations in greenhouse land were significantly higher than in crop land and wood land ( p < .05). Based on principal component analysis, elevated Cu, Zn, and Cd concentrations in greenhouse land might have originated from high application rates of manure and fertilizer. According to an ecological risk analysis, the four land use types can be ranked in the following order: greenhouse land > orchard land > crop land > wood land. However, the degree of non-cancer risk for both adults and children in different land uses decreased in the order of greenhouse land > orchard land > wood land > crop land.